Marketing Communication Strategy through Social Media on TikTok Account @balemangrove_jrw to Increase Brand Awareness (November - December 2024 Periode) - Hadi Tsani, Habib Rakhman; Mulawarman, Krisna (Jogjakarta Communication Conference (JCC), 2025)
This study discusses the marketing communication strategy through TikTok social media on the @balemangrove_jrw account to increase brand awareness of the Bale Mangrove Jerowaru ecotourism destination. The background of this study is the high potential of social media, especially TikTok, as an effective promotional tool in the environmental tourism sector. This study uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation. The results of the study show that the use of TikTok as the main promotional medium with attractive visual content, utilization of trends, and interactive communication strategies has succeeded in attracting audience attention, encouraging tourist visits, and increasing Bale Mangrove brand awareness. This strategy is balanced with an educational approach and collaboration with influencers to expand the promotion reach. In conclusion, TikTok is an effective medium for building the image of a tourist destination, especially among the younger generation who are active in the digital world.